Occupational Therapy Assessments of Cortical or Cerebral Visual Impairment: A Systematic Review. - Weisser-Pike, Orli; Mitchell, Anita Witt; Cordova, Leah (American Journal of Occupational Therapy)
Importance: Cortical or cerebral visual impairment (CVI), a leading cause of visual dysfunction in children across the globe, can result in delayed development of fine and gross motor skills, functional mobility, and socialization, which affects all areas of occupation. No assessments are recommended for occupational therapy practitioners working with children with CVI. Objective: To appraise the measurement properties and clinical utility of CVI assessments appropriate for use by occupational therapy practitioners. Data Sources: MEDLINE via PubMed, Scopus, and Web of Science. Study Selection and Data Collection: We followed the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) guidelines for systematic reviews of patient-reported outcome measures for relevant studies. Findings: A total of 590 records yielded 15 studies of the measurement properties of 12 assessment tools, 8 patient-reported outcome measures and 4 clinician-reported or performance-based outcome measures. We report on the quality of measurement properties of 10 of the 12 outcome measures. None had high-quality evidence of content validity, structural validity, or test–retest reliability. Most had indeterminate internal consistency as a result of a lack of confirmatory factor analysis. Three instruments demonstrated high quality and sufficient construct validity. Conclusions and Relevance: On the basis of the COSMIN guidelines, all 12 outcome measures have the potential to be recommended but require further study before definitive recommendations can be made. What This Article Adds: This is the first systematic review of assessments of CVI feasible for use by occupational therapy practitioners. High-quality studies of measurement properties are lacking. Further examination of the measurement properties of outcome measures is required. This is the first systematic review of assessments of cortical or cerebral visual impairment (CVI) feasible for use by occupational therapy practitioners.